Prototipe Komik Hadis sebagai Media Pembelajaran Hadis: Studi Hadis tentang Ketenangan Hati - Hilwa Zahratul Jannah Nurfalah (UIN Sunan Gunung Djati Bandung, 2026)
This research was conducted based on the urgency of hadith learning for society, the low interest in reading in Indonesia, and the difficulty of finding inner peace in modern times. Therefore, the author initiated the development of a prototype hadith comic as a learning medium focusing on inner peace. The objectives of this research are to produce a prototype hadith comic about inner peace, identify the media and production process involved, and identify the hadiths used in the comic. The development of the hadith comic prototype employed a qualitative method with a literature study approach. Several supporting media were used in the production process, including Al-Manshah Al-Hadisiyah, Google Scholar, Microsoft Word, and Clip Studio Paint. The production process consisted of several stages: searching for relevant hadiths and data, recording and writing the substance, designing the comic, and conducting an evaluation. The hadith comic prototype consists of six chapters containing ten hadiths as its main content. The prototype was then titled “Hadasana: Kuatkan Diri Tenangkan Hati” and subsequently registered for an ISBN as an official identification for the book. This research has limitations, particularly because the discussion remains relatively general and lacks depth.